Complex care and contradictions of choice in the safety net. Issue 3 (8th February 2018) - Van Natta, Meredith; Burke, Nancy J.; Yen, Irene H.; Rubin, Sara; Fleming, Mark D.; Thompson‐Lastad, Ariana; Shim, Janet K.
Abstract: This article explores the complicated and often‐contradictory notions of choice at play in complex care management (CCM) programmes in the US healthcare safety net. Drawing from longitudinal data collected over two years of ethnographic fieldwork at urban safety‐net clinics, our study examines the CCM goal of transforming frequent emergency department (ED) utilisers into 'active' patients who will reduce their service utilisation and thereby contribute to a more rational, cost‐effective healthcare system. By considering our data alongside philosopher Annemarie Mol's (2008) conceptualisation of the competing logics of choice and care, we argue that these premises often undermine CCM teams' efforts to support patients and provide the care they need – not only to prevent medical crises, but to overcome socio‐economic barriers as well. We assert that while safety‐net CCM programmes are held accountable for the degree to which their patients successfully transform into self‐managing, cost‐effective actors, much of the care CCM staff provide in fact involves attempts to intervene on structural obstacles that impinge on patient choice. CCM programmes thus struggle between an economic imperative to get patients to make better health choices and a moral imperative to provide care in the face of systemic societal neglect. (A virtual abstract of this paper can be viewed at:https://www.youtube.com/channel/UC_979cmCmR9rLrKuD7z0ycA ).